Entrance gate flanked by two carved pillars - Temples of India Project Team (Jio Institute, 2024)
A closer view of an entrance on the north side of the temple premises. This entrance might not be the original entrance as there is a high possibility that the main entrance was located at the front and not to the side of the temple. But currently, this entrance serves as the main entrance with a metal gate, flanked by two carved pillars. On both sides of the entrance, broken fragments of the temple are arranged to form a boundary wall around the temple complex.